Tislelizumab induced dual organs dysfunction in a patient with advanced esophageal squamous cell carcinoma: a case report - Yang, Bo; Gou, Wei; Lan, Naiying; Shao, Qing; Hu, Weifeng; Xue, Cheng; Liu, Nanmei (Frontiers in Oncology, 2024)
Background Tislelizumab, a humanized IgG4 anti-PD-1 monoclonal antibody has been approved in China and Europe. According to the published clinical research, tislelizumab shows satisfactory safety profile. No severe hepatotoxicity or acute kidney injury were reported. Case presentation We presented a case study of a 74-year-old man who developed acute kidney injury (grade 3) and acute liver injury (grade 4) after being administered tislelizumab for the treatment of esophageal squamous cell carcinoma. We reviewed the patient’s history, physical examination, and laboratory findings and provided comprehensive differentials of the possible causes of the toxicities. Immune Checkpoint Inhibitors (ICI) hepatotoxicity and nephrotoxicity were confirmed clinically. We also discussed the management of toxicities associated with ICIs and the need for a multidisciplinary approach to care. Conclusions The case highlights the importance of close monitoring and prompt management of toxicities associated with ICIs and the need for further research to better understand the risk factors for these toxicities and to identify effective treatments for them.